CULTURAL AND BEHAVIORAL TRANFORMATION: THE ROLE OF LEADERSHIP, COMPENSATION, WORK ENVIRONMENT CORPORATE VALUE ON EMPLOYEE PERFORMANCE - Subariyanti, Herudini; Yulianto, Andri Rizko; Sari, Dina Purnama; Harun, Muhamad (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
This study examines the relationship between corporate values, leadership, compensation, and work environment in influencing employee performance, emphasizing the integration of corporate  value as a moderating factor. Using the AKHLAK core values adopted by Indonesian State-Owned Enterprises (BUMN) as a foundation, the research highlights the significance of shared cultural principles in fostering alignment, ethical behavior, and organizational success. The study underscores the importance of transformational leadership, equitable compensation, and a supportive work environment in improving performance while moderated by corporate value. The AKHLAK framework, launched in 2020, aims to standardize behaviors across BUMN and foster collaboration, innovation, and adaptability. Employing a qualitative literature review, this study proposes a conceptual model to guide policymakers in integrating spirituality into corporate culture, enhancing employee motivation and engagement, and driving sustainable organizational transformation in a competitive and dynamic environment